Beyond Conflicts : Cultural and Religious Cohabitations in Alexandria and Egypt between the 1st and the 6th Century CE - Arcari, Luca (Studien und Texte zu Antike und Christentum Studies and Texts in Antiquity and Christianity, 2017)
Cover -- Acknowledgements -- Table of Contents -- Abbreviations -- Introduction -- Luca Arcari: Cultural and Religious Cohabitations in Alexandria and Egypt between the 1st and the 6th Cent. CE -- 1. Methodological issues -- 1.1. Constructing collective "identities" -- 2. Religious and cultural cohabitations in Egypt and Alexandria(1st-6th cent. CE) -- 2.1. A regional approach in light of the integration between different sources -- 2.1.1. "Pervasive" cultural centres -- 2.1.2. Local reinventions of tradition -- 2.2. The limits of the "traditional" taxonomies -- 3. Structure and contents of the book -- Bibliography -- Part One: Use, (Re-)Invention And (Re-)Definitionof Discursive Practices -- Tobias Nicklas: Jewish, Christian, Greek? The Apocalypse of Peter as a Witness of Early 2nd-Cent. Christianity in Alexandria -- 1. The Apocalypse of Peter - Jewish, Christian, or other? -- 2. Results regarding the text's alleged place and context of origin -- 3. Conclusion -- Bibliography -- Philippe Matthey: The Once and Future King of Egypt: Egyptian "Messianism" and the Construction of the Alexander Romance -- 1. The Egyptian origins of the Alexander Romance -- 2. "Apocalyptic" literature in Hellenistic and Roman Egypt -- 3. Apocalyptic elements in the Alexander Romance -- 4. Development of the Graeco-Egyptian "apocalypticism" -- 5. Historical theodicy in Egypt -- 6. Production of "apocalyptic" literature in ancient Egypt. A conclusion -- Bibliography -- Antonio Sena: Demonology between Celsus and Origen: A Theoretical Model of Religious Cohabitation? -- 1. Origen's education and Celsus' background -- 2. Demonology as an integration proposal -- 3. A model of cultic integration -- Bibliography -- Daniele Tripaldi: "Basilides" and "the Egyptian Wisdom:" Some Remarks on a Peculiar Heresiological Notice (Ps.-Hipp. Haer. 7.20-27).